Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

kushashwa23

  • 4 years ago

2x+3=-4x-9y 2x+8y=3-4x can i solve this question with substitution method

  • This Question is Closed
  1. kushashwa23
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    2x+4x=-9y-3 2x+4x=-8y+3 - - = + - 0 = -y-6 6=-y y=-6 m i going right

  2. alexray19
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    That's not the substitution method; that's subtraction. Because you solved them both to equal 2x+4x, you could substitute them by taking the right-hand sides of both of the equations and setting them equal to each other:\[-9y-3=-8y+3\]Then solve for y:\[9y=8y-6\]\[y=-6\]

  3. AdequateDisclosure
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    |dw:1316128480617:dw|

  4. kushashwa23
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    thanks every one

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy